Ketersediaan Tinggi Website menggunakan Penskalaan Otomatis dan Penyeimbang Beban AWS - Haeruddin, Haeruddin; Andik Yulianto; Stefanus Eko Prasetyo; Gautama Wijaya; Dominggo Givarel (Telcomatics, 2025)
The rapid development of information technology requires digital service systems to have high performance and optimal availability. One of the main challenges in managing web-based services is the system's ability to deal with an unpredictable surge in the number of users. If not anticipated, this can cause a decrease in performance and even detrimental downtime. This study aims to analyze and implement the concept of auto scaling and load balancing in an effort to improve the performance and availability of web-based services. Auto scaling functions to automatically adjust the number of server resources according to workload needs, while load balancing plays a role in distributing network traffic evenly to several servers. The research method used is an experiment, by implementing and testing service performance before and after the implementation of auto scaling and load balancing. The test results show that the combination of the two technologies is able to increase the speed of service response, reduce server load, and maintain optimal service availability. This research is expected to be a reference in the development of reliable and efficient cloud-based systems.